Direct Waveguide Writing with High Energy High Repetition Rate Picosecond Laser Pulses - Alexeev, Ilya; Cvecek, Kristian; Genser, Jan; Schmidt, Michael (Elsevier BV, 2012)
Direct femtosecond pulse laser waveguide writing based on laser induced localized modification of the refractive index of bulk glass can be a versatile fabrication method for many micro applications. Although the method's potentials have been realized its application is still rather limited, either due to the slow writing speeds caused by low laser pulse repetition rates of amplified systems or due to the shallow structuring depths restricted by low pulse energies of nonamplified lasers. In this work we investigate the direct waveguide writing process using a picosecond laser that allows fast and deep waveguide writing due to high pulse energies available at high pulse repetition frequencies. (C) 2012 Published by Elsevier B. V. Selection and/or review under responsibility of Bayerisches Laserzentrum GmbH
Keywords: direct waveguide writing; ultrafast micromachining